(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to a comprehensive analysis of the anatomical and physiological features of the human respiratory system and the mechanisms of its adaptation to changes in the functional state of the body. The respiratory system plays a key role in maintaining homeostasis by ensuring gas exchange between the external environment and the cells, thereby determining the level of energy supply. The efficiency of its functioning becomes particularly relevant under conditions of increased energy demands. The paper examines the morphological and functional characteristics of the respiratory system, including the anatomical structure of the lungs, airways, and respiratory muscles, as well as the specific features of neurohumoral regulation of ventilation processes. Special attention is paid to the responses of the respiratory system to elevated metabolic demands arising during the activation of motor activity. It has been established that regular physical exercise stimulates the development of adaptive changes, manifested in increased vital capacity of the lungs, improved strength and endurance of the respiratory muscles, more economical breathing patterns, and enhanced regulation of respiratory function. The study provides a comparative analysis of vital capacity (VC), forced vital capacity (FVC), and forced expiratory volume in one second (FEV1) among higher education students who do not engage in sports and those who regularly participate in sports training. The results demonstrated significantly higher functional indicators in the group of physically active students, confirming the positive impact of systematic motor activity on the functional state of the respiratory system. Despite the considerable number of studies in this field, the complex analysis of the relationship between morphological characteristics of the respiratory apparatus and the specificity of regulatory mechanisms of gas exchange remains insufficiently explored. This highlights the need for further research aimed at clarifying individual adaptive responses, improving methods for assessing pulmonary reserve capacity, and developing practical recommendations for optimizing motor activity. The practical significance of the findings lies in their potential application in sports, physical rehabilitation, preventive medicine, and the educational process. They may contribute to enhancing the effectiveness of training programs, developing individualized approaches to exercise prescription, and improving the system of professional training in the field of physical education and sports.